Seasonal lake surface water temperature trends reflected by heterocyst glycolipid-based molecular thermometers - Bauersachs, T.; Rochelmeier, J.; Schwark, Lorenz (Copernicus GmbH, 2015)
It has been demonstrated that the relative distribution of heterocyst glycolipids (HGs) in cultures of N2-fixing heterocystous cyanobacteria is largely controlled by growth temperature, suggesting a potential use of these components in paleoenvironmental studies. Here, we investigated the effect of environmental parameters (e.g., surface water temperatures, oxygen concentrations and pH) on the distribution of HGs in a natural system using water column filtrates collected from Lake Schreventeich (Kiel, Germany) from late July to the end of October 2013. HPLC-ESI/MS (high-performance liquid chromatography coupled to electrospray ionization–mass spectrometry) analysis revealed a dominance of 1-(O-hexose)-3,25-hexacosanediols (HG26 diols) and 1-(O-hexose)-3-keto-25-hexacosanol (HG26 keto-ol) in the solvent-extracted water column filtrates, which were accompanied by minor abundances of 1-(O-hexose)-3,27-octacosanediol (HG28 diol) and 1-(O-hexose)-3-keto-27-octacosanol (HG28 keto-ol) as well as 1-(O-hexose)-3,25,27-octacosanetriol (HG28 triol) and 1-(O-hexose)-3-keto-25,27-octacosanediol (HG28 keto-diol). Fractional abundances of alcoholic and ketonic HGs generally showed strong linear correlations with surface water temperatures and no or only weak linear correlations with both oxygen concentrations and pH.Changes in the distribution of the most abundant diol and keto-ol (e.g., HG26 diol and HG26 keto-ol) were quantitatively expressed as the HDI26 (heterocyst diol index of 26 carbon atoms) with values of this index ranging from 0.89 in mid-August to 0.66 in mid-October. An average HDI26 value of 0.79, which translates into a calculated surface water temperature of 15.8 ± 0.3 °C, was obtained from surface sediments collected from Lake Schreventeich. This temperature – and temperatures obtained from other HG indices (e.g., HDI28 and HTI28) – is similar to the one measured during maximum cyanobacterial productivity in early to mid-September and suggests that HGs preserved in the sediment record of Lake Schreventeich reflect summer surface water temperatures. As N2-fixing heterocystous cyanobacteria are widespread in present-day freshwater and brackish environments, we conclude that the distribution of HGs in sediments may allow for the reconstruction of surface water temperatures of modern and potentially ancient lacustrine settings.